Chronic myeloid leukemia with pure erythroid leukemia blast crisis. Issue 1 (2nd January 2022) - Jacobs, Jeremy W.; Ramaswamy, Rahul; States, Vanessa; Reppucci, Jennifer; Oluwole, Olalekan O.; Mason, Emily F.; Thompson, Mary Ann
Abstract: Chronic myeloid leukemia (CML), a myeloproliferative neoplasm defined by the presence of the BCR-ABL1 oncogene created by the reciprocal translocation t (9;22)(q34.1;q11.2), can often be controlled by medications that inhibit this constitutive tyrosine kinase. However, if these therapies fail, the disease may progress to a form resembling an acute leukemia. While most of these CML 'blast crises' are characterized by blasts with a myeloid (granulocytic) or lymphoid lineage, these blasts may rarely be predominantly erythroid. Cases of CML erythroid blast crises have been reported; however, secondary pure erythroid leukemia arising from a CML blast crisis has only been definitively reported once before. We report the second definitive case of pure erythroid leukemia with the t (9;22)(q34.1;q11.2) presenting as a CML blast crisis and characterize the morphologic, immunophenotypic, flow cytometric, cytogenetic, and molecular findings.